Answer:
15
Step-by-step explanation:
googled it
Answer:
7. (4x +10)/(x^3 +3x^2 -16x -48)
9. -320/93
Step-by-step explanation:
7. As with adding any fractions, first you find a common denominator. When the fractions are rational expressions, it often helps to factor the denominators.
6/(x^2 -16) -2/(x^2 -x -12) = 6/((x -4)(x +4)) -2/((x -4)(x +3))
= (6(x +3) -2(x +4))/((x -4)(x +3)(x +4)) . . . . . using a common denominator
= (6x +18 -2x -8)/((x -4)(x +3)(x +4))
= (4x +10)/((x^2 -16)(x +3))
= (4x +10)/(x^3 +3x^2 -16x -48)
_____
9. First you simplify the denominator:
2/25 -5/16 = (2·16 -5·25)/(25·16) = -93/400
Then you perform the division. This can be done by multiplying by the inverse of the denominator.
(4/5)/(2/5 -5/16) = (4/5)·(-400/93) = -320/93
Answer:
so idc![\sqrt[n]{x} \sqrt{x} \alpha \pi x^{2} \\ \left \{ {{y=2} \atop {x=2}} \right. x_{123} \int\limits^a_b {x} \, dx \lim_{n \to \infty} a_n \left[\begin{array}{ccc}1&2&3\\4&5&6\\7&8&9\end{array}\right]](https://tex.z-dn.net/?f=%5Csqrt%5Bn%5D%7Bx%7D%20%5Csqrt%7Bx%7D%20%5Calpha%20%5Cpi%20x%5E%7B2%7D%20%5C%5C%20%5Cleft%20%5C%7B%20%7B%7By%3D2%7D%20%5Catop%20%7Bx%3D2%7D%7D%20%5Cright.%20x_%7B123%7D%20%5Cint%5Climits%5Ea_b%20%7Bx%7D%20%5C%2C%20dx%20%20%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20a_n%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%262%263%5C%5C4%265%266%5C%5C7%268%269%5Cend%7Barray%7D%5Cright%5D)
443
Step-by-step explanation: its 2 6\7
T - 76 = 0
If you switch it around, it becomes:
0 + 76 = t
0 + 76 = 76
t = 76
~Hope this helped~
Answer: option B is correct.
Step-by-step explanation:
The equation of a straight line can be represented in the slope-intercept form, y = mx + c
Where c = intercept
Slope, m =change in value of y on the vertical axis / change in value of x on the horizontal axis represent
change in the value of y = y2 - y1
Change in value of x = x2 -x1
y2 = final value of y
y 1 = initial value of y
x2 = final value of x
x1 = initial value of x
The line passes through (- 5, - 2) and (3, - 1),
y2 = - 1
y1 = - 2
x2 = 3
x1 = - 5
Slope,m = (- 1 - - 2)/(3 - - 5) = 1/8
To determine the intercept, we would substitute x = 3, y = - 1 and
m = 1/8 into y = mx + c. It becomes
- 1 = 1/8 × 3 + c
- 1 = 3/8 + c
c = - 1 - 3/8 = - 11/8
The equation becomes
y = x/8 - 11/8